Robotic Plasma Probe Ionization Mass Spectrometry (RoPPI-MS) of Non-Planar Surfaces - Bennet, Rachel V. (2014)
In this report, we present a robotic sample introduction/ionization system for mass spectrometry (MS) for spot analysis and imaging of non-planar surfaces. The system operates by probing the sample surface with an acupuncture needle, followed by direct plasma chemical ionization time-of-ﬂight MS.